The Soul of the Frog for a Postmodern Age - Miller, Gordon L. (Zygon, 2024)
The history of modern science bears abundant witness to the fact that the humble frog has yielded myriad insights into the intricacies of anatomy and physiology far beyond frogs, producing several Nobel laureates in the process. A concurrent but less heralded inquiry and debate, however, has wrestled with the harder question of, as Thomas Henry Huxley put it in 1870, "Has a Frog a Soul?," with frogs serving as convenient experimental subjects for issues of the human soul and body. Here, I present highlights from this debate among leading eighteenth- and nineteenth-century scientists representing animistic and burgeoning mechanistic views, with the latter effecting a significant contraction of soul, ending with William James in 1890. I then bring the inquiry up to date by showing how Alfred North Whitehead’s philosophy of organism and some recent physiological research offer promising and constructive postmodern hope for addressing the dispiriting loss of soul, on various levels, that afflicts much of modern life.